O terrorismo e a multiplicidade de interpretação: a lógica racional das Teorias Racionalistas, a construção discursiva das Teorias Reflexivistas e as Relações Internacionais - Brandão, Wildson Roberto Lima (2020)
The purpose of this analysis is to identify how the phenomenon of terrorism is interpreted based on the perspectives of the two major theoretical groups within this specific field of study within the greater field of International Relations, such groups being that of rationalist theories and that of reflexivist theories, and how such sets position themselves in face of interpretation of the phenomenon of terrorism itself and its interactions. This work aims to demonstrate how each of these two theoretical categories interprets and designates to the phenomenon of terrorism their own differentiations and explanations, and also how, derived from each of the already mentioned definitions, the different forms of counterterrorist action are derived, whether these are direct actions, coming from the rationalist group or indirect actions, derived from the theoretical reflexivist group. In addition, this work tries to interpret the expansion and even the limitations that each of these groups infers to the studies of terrorism